Influence of Antioxidants on Physio-Chemical Properties of the Mixture of Rice Bran Oil and Rapeseed Oil for Transformers - Dung, Nguyen Van; Liem, Pham Thanh; Anh, Trinh Quoc (VNU Journal of Science: Natural Sciences and Technology; Vol 37 No 2, 2021)
This study evaluated the effect of antioxidants on the physical and chemical parameters of a mixture of rice oil and rape-seed oil for using as insulating transformer oil. Antioxidants such as butylated hydroxytoluene, tertiary butyl hydroquinone and propyl gallate were used. Experimental results showed that these three additives increased the oxidation stability index of the oil mixture, but tertiary butyl hydroquinone had the greatest effect and increased the oxidation stability index by 4 times. However, tertiary butyl hydroquinone insignificantly changes the physical and chemical parameters of the oil mixture except for the breakdown strength. This parameter of the oil mixture was increased by about 24% when tertiary butyl hydroquinone (0,3 wt%) was added. In addition, it was observed that tertiary butyl hydroquinone inhibited the aging process of the oil mixture at high temperatures. With the presence of tertiary butyl hydroquinone, the viscosity of the aged oil mixture only increased by 16% instead of up to 36% in case of without addition of the antioxidant under without oxygen or low concentration of oxygen.